El archivo de la Escuela Superior de Diplomática - García Medina, Amelia (Revista General de Información y Documentación, 2007)
On the occasion of the celebration of hundred fiftyth aniverssary of the “Escuela Superior de Diplomática” creation, it was celebrated a conference sing on 13th and 14th of the last December in the Document’s Sciences Faculty. The topic of this article was the subject of one of the lectures, and, for its interest, we have believed opportune its publication. It is a question of a study of the funds generated by “Escuela de Diplomática” in the development of its activity. We have analyzed its archive’s history, its dispersion, if it occurred, and published the organization of the documents in the Historical Archive of University of Madrid, in a more detailed way than in other articles.